1987
DOI: 10.1038/326698a0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NMDA receptors blocks GABAergic inhibition in an in vitro model of epilepsy

Abstract: The application of tetanic electrical stimuli to the stratum radiatum fibre pathway in the hippocampus in vitro produces an NMDA (N-methyl-D-aspartate) receptor-dependent enhancement of synaptic efficacy. Repeated application of such stimuli produces a progressive enhancement of synaptic efficacy leading to the genesis of spontaneous and stimulation-evoked epileptiform discharges. We have used this in vitro approach to explore the cellular mechanisms which underlie the kindling model of epilepsy. Kindling of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
101
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(105 citation statements)
references
References 20 publications
4
101
0
Order By: Relevance
“…In conclusion, the plasticity observed directly at interneuron excitatory synapses indicates that synaptic efficacy in hippocampal inhibitory networks is modifiable according to hebbian rules and thus represents a mechanism by which long-term synaptic plasticity in inhibitory networks might contribute to complex information processing in the hippocampus (10,11). The observation that TBS paired with depolarization is an effective stimulation paradigm for its induction further suggests that such synaptic plasticity may take place in a behaviorally relevant context, for instance, during hippocampal theta activity (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the plasticity observed directly at interneuron excitatory synapses indicates that synaptic efficacy in hippocampal inhibitory networks is modifiable according to hebbian rules and thus represents a mechanism by which long-term synaptic plasticity in inhibitory networks might contribute to complex information processing in the hippocampus (10,11). The observation that TBS paired with depolarization is an effective stimulation paradigm for its induction further suggests that such synaptic plasticity may take place in a behaviorally relevant context, for instance, during hippocampal theta activity (41).…”
Section: Discussionmentioning
confidence: 99%
“…Modeling studies suggest that plasticity at interneuron synapses is important for learning and recall by hippocampal neuronal networks (9). However, experimental evidence of long-term synaptic plasticity at input and͞or output synapses of hippocampal interneurons has been controversial (10)(11)(12)(13)(14)(15)(16). This uncertainty has been due, in part, to the heterogeneity of interneuron types present in the hippocampus and to the complexity of the network (6,17,18).…”
mentioning
confidence: 95%
“…Although the exact function of GABAergic inhibition in the integrative activity of the cortex remains unclear, its importance is underscored by studies showing that the pharmacological blockade of GABAA receptor lead to epileptiform activity (Schwartzkroin & Prince, 1980) and that deficiencies in the GABAergic inhibitory system may be involved in some forms of human epilepsy (Lloyds, Bossi, Morselli, Munari, Rougier & Loiseau, 1986). In addition, modification of inhibition may be involved in both short-term (Ben-Ari, Krnjevic & Reinhardt, 1979;XXTong & Wlatkins, 1982;McCarren &, Alger, 1985;Thompson & Gaehwiler, 1989) and long-term (Stelzer, Slater & ten Bruggencate, 1987; Miles & Wong, 1987) changes in neuronal activity following tetanic stimulation of afferent fibres to the hippocampus. Simulation studies (Traub, Miles & Wong, 1989), based on data obtained from the hippocampal slice preparation, showed that reverberating, synchronized activity appears in groups of hippocampal cells when inhibition is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The induction of LTD of GABA A receptor-mediated IPSCs (GABA A R-IPSCs) requires activation of excitatory NMDA receptors (Stelzer et al, 1987). The biochemical links between the NMDA receptors and the pathway for inducing LTD of GABA A R-IPSCs involve calcineurin (CaN) (Lu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A brief high-frequency stimulation (tetanus) of the Schaffer-collateral fibers produces long-term potentiation (LTP) of EPSCs and concomitantly longterm depression (LTD) of IPSCs (Andersen and LĂžmo, 1968;Stelzer et al, 1987;Lu et al, 2000). These coordinately regulated bidirectional changes of the excitatory and inhibitory synaptic strength are considered to be a cellular model of learning and memory (Bliss and Collingridge, 1993;Paulsen and Moser, 1998).…”
Section: Introductionmentioning
confidence: 99%